Greening with exotics Mount Makiling and reforestation discourses in the twentieth-century Philippines - Pagunsan, Ruel V. (Philippine Studies: Historical and Ethnographic Viewpoints, 2023)
This article historicizes the use of exotic trees in Philippine greening projects. Highlighting the development of Mount Makiling into a forest laboratory where different exotic species were experimented on before their transplantation. It shows that colonial understanding regarding the role of exotic species in reforestation continued to shape postcolonial efforts. I argue that the use of Makiling as a "natural laboratory" for countrywide projects produced conflicting discourses about the relationship between nature and nation, and that the changing appreciation toward exotic trees was guided not only by biological studies but also interests framed within the ideas of national identity and development.